The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1308/rcsbull.2020.179
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sex, race and the hidden curriculum on medical students' career choices: lessons for orthopaedics

Abstract: With falling applicant numbers, we investigate the factors that have a negative impact on students' perception of trauma and orthopaedics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Among women who did not wish to pursue T&O, 63.1% stated that a high male to female ratio and perception of a male-dominant culture of T&O influenced their decision (Figure 2a). These findings are concordant with past studies that showed that the absence of a "critical mass" of women discouraged them from pursuing T&O (14,22). Women that eventually enter orthopaedic training often encounter unconscious bias, microaggressions, and discriminatory language that may make them feel excluded (23).…”
Section: Male Dominant Culture In Tandosupporting
confidence: 87%
See 1 more Smart Citation
“…Among women who did not wish to pursue T&O, 63.1% stated that a high male to female ratio and perception of a male-dominant culture of T&O influenced their decision (Figure 2a). These findings are concordant with past studies that showed that the absence of a "critical mass" of women discouraged them from pursuing T&O (14,22). Women that eventually enter orthopaedic training often encounter unconscious bias, microaggressions, and discriminatory language that may make them feel excluded (23).…”
Section: Male Dominant Culture In Tandosupporting
confidence: 87%
“…Despite the development of new techniques and equipment, T&O is still viewed as a speciality that requires physical strength for the completion of procedural tasks (8,14).…”
Section: Technical Aspects Of Orthopaedic Surgerymentioning
confidence: 99%
“…7 These myths are often perpetrated by other specialties with an outdated view of our speciality. 8 It has been shown that medical students are more likely to pursue orthopaedics if they see themselves as having the same traits as the traditional 'white, athletic, male' orthopaedic surgeon. 9 However, diversity has repeatedly been shown to improve innovation and patient outcomes, [10][11][12] so we need to work harder to make a career in orthopaedics accessible to all.…”
mentioning
confidence: 99%
“…In addition, the subspecialty is often perceived as an old boys' club, where sexism is prevalent and women are disadvantaged. 3,6 Whether or not these stereotypes are based in truth, it is often the perception of orthopaedic surgeons to those outside the specialty, including medical students who have yet to decide their career path. 3 The importance of role models cannot be over emphasized in the recruitment of future orthopaedic surgeons.…”
Section: Current Culture In Orthopaedicsmentioning
confidence: 99%